2020
DOI: 10.4067/s0718-88702020000100075
|View full text |Cite
|
Sign up to set email alerts
|

The choice of elderly labor: Evidence from Ecuador

Abstract: What drives elderly people decide to work after retirement? This paper analyzes the economic determinants of the decision to work in Ecuadorian elderly. In the analytical part, authors have analyzed the literature devoted to the study of elderly people, from which several testable hypotheses that relate it to income, education level and complex household have been derived. The article provides empirical evidence from using the Living Conditions Survey (2014). The estimation results suggest that variables as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Mueen Nasir et al (2000) explain that the number of family members who generate income as a proxy of total family income is negatively related to the employment decisions of the elderly in Pakistan. Research by Lanchimba et al (2020) in Ecuador found that the variable of labour income from the elderly has a positive effect on the possibility of continuing to work in old age. This strengthens the notion that the elderly work mostly because of economic factors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mueen Nasir et al (2000) explain that the number of family members who generate income as a proxy of total family income is negatively related to the employment decisions of the elderly in Pakistan. Research by Lanchimba et al (2020) in Ecuador found that the variable of labour income from the elderly has a positive effect on the possibility of continuing to work in old age. This strengthens the notion that the elderly work mostly because of economic factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The determinants of the elderly’s decision to participate in economic activities as measured by work participation have been the subject of researches. Among them are done by Chang and Yen (2011), Hill (2002); Kooij et al (2008), Lanchimba et al (2020); Mueen Nasir et al (2000); and Sun et al (2011).…”
Section: Literature Reviewmentioning
confidence: 99%